2016 Applied Aerodynamics Conference : evolution & innovation continues : the next 150 years of concepts, design and operations : conference programme & proceedings : 19-21, July 2016, Bristol. (Royal Aeronautical Society, 2016)
The Royal Aeronautical Society is proud to announce that its next biennial Applied Aerodynamics Research Conference will take place in Bristol between the 19 - 21 July 2016. Aviation is growing steadily, traffic forecasts suggest doubling over the next two decades and the need for efficient and sustained growth is recognised. Currently there are several international research programmes as well as the European and UK collaborative research projects, aimed at encouraging improved efficiency and greener aviation for all types of speeds, payloads and ranges via novel design and/or operations (e.g. clean sky, cruiser - feeders, laminar flows, morphing etc ...). These civil aviation led research initiatives are also impacting on military research. There are many researchers spearheading the knowledge base needed. It is proposed that the conference will devote special sessions to focus on discussions and dissemination from these initiatives. --